Mechatronic design for signal processor for recycling TVs - Vunnam Ramarao. (2008)
Television (TV) technology is changing from analog to digital making a large number of analog TVs redundant. This poses a big challenge to the environmental friendly recycling process. In this report, an attempt is made to propose a recycling plan to convert analog TVs for digital usage.